Middle Income Trap Di Indonesia Dan Analisisnya - Rifki Khoirudin; Okta Rian Widyastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Countries with developing status are starting to experience quite rapid economic growth, especially in the Asian region. It can be seen in Indonesia in 2000, experiencing an increase in income, but has not been able to change Indonesia's status. This study aims to analyze the determinants of per capita income, which is useful for removing Indonesia from developing country status. By analyzing the effect of Gross Fixed Capital Formation (PMTB), Agricultural Value Added, FDI and Inflation on capita which is the basis for grouping income of countries in the world. The variables used are per capita income, formation of gross fixed capital (PMTB), agricultural value added (NTP), (FDI), exports and inflation in 1980-2019. The results of the linear regression carried out show that the Variable Farmer Exchange Rate (NTP) is not significant to Per Capita Income, the PMTB ratio has a positive and significant effect on Per Capita Income, Foreight Direct Investment (FDI) is not significant to Per Capita Income, Exports have a positive effect and significant to Per Capita Income, Inflation has a negative and significant effect on per capita income. Keywords: Linear Regression, Middle income trap, Per Capita Income.